Second Transurethral Resection of Bladder Tumor: Is it Necessary in All T1 and/or High-Grade Tumors? - Ayati, Mohsen; Amini, Erfan; Shahrokhi Damavand, Reza; Nowroozi, Mohammad Reza; Soleimani, Mohammad; Ranjbar, Ehsan; Nowroozi, Ali (Urology Journal, 2019)
Purpose: To evaluate the role of second transurethral resection of bladder tumor (TURBT) in patients with T1 and/or high-grade bladder tumor regarding tumor size, multiplicity, and presence or absence of muscle in specimens of initial resection. Materials and Methods: A total of 107 patients with either primary T1 or high-grade urothelial bladder cancer underwent second TURBT within 6 weeks after initial surgery and prior to starting intravesical immunotherapy. We assessed the incidence of residual disease and upstaging in second TURBT. Results: Upstaging was noted in 11 (10.3%) patients and residual tumor was evident in 29 (27%) patients. Disease upstaging had a statistically significant association with tumor size, multifocality, and absence of muscle at initial resection in univariate analysis. Presence of residual tumor in second resection also showed significant association with tumor size and absence of muscle at initial resection but not multifocality. Multivariate logistic regression analysis revealed that absence of muscle at initial resection independently predicts disease upstaging during second TURBT (OR = 8.123, 95% CI: 1.478-44.632). Furthermore, both tumor size (OR = 13.573, 95% CI: 3.104-59.359) and absence of muscle (OR = 21.214, 95% CI: 6.062-74.244) were independent predictors of residual disease in second TURBT. Conclusion: We showed that second TURBT in a subset of patients with single, small T1 and/or high-grade tumor who underwent complete initial resection might be of limited value.